HUBUNGAN TINGKAT PENGETAHUN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DENGAN PENCEGAHAN PENYAKIT PEDIKULOSIS KAPITIS PADA SANTRIWATI DI PONDOK PESANTREN MODERN DAARUL MUTTAQIEN 1 CADAS SEPATAN TANGERANG - Novita Rosdiana; Siti Rochmani (Nusantara Hasana Journal, 2021)
Knowledge or cognitive is a very important domain in shaping one's actions (overt behavior). Clean and healthy life behavior PHBS is one of the factors of the occurrence of disease transmission problems in certain circumstances, pediculosis capitis disease is one of the diseases caused by unfavorable room environment. Pediculosis capitis is a skin disease that attacks human hair and can cause head lice. Research Objectives: This is to know the relationship between the level of knowledge of clean and healthy living behavior of PHBS with the prevention of pediculosis capitis in female students at Pondok Pesantren Modern Daarul Muttaqien 1 Cadas Tangerang Research Methods: This study uses a descriptive correlation design using cross sectional design so that 120 respondents are obtained with the chi square test statistical analysis technique. Research Results: Based on the results of the statistical test used is univariate and bivariate analysis using the chi square test and correlation person in the existence of a relationship between the level of knowledge of PHBS with the prevention of pediculosis kaptis disease, as evidenced by the results of P-value 0,000 <0.05. Conclusion: From the results of this study which means there is a relationship that has a low closeness.